2019
DOI: 10.1007/s40744-019-0153-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Patient Experience on the Path to Diagnosis of Ankylosing Spondylitis

Abstract: Introduction We describe the journey to diagnosis of ankylosing spondylitis (AS) from the patient perspective and examine differences in this journey by sex. Methods US adults aged ≥ 18 years with a self-reported AS diagnosis were recruited online through CreakyJoints, a patient support community, and ArthritisPower, a patient research registry. Respondents completed a web-based survey on sociodemographics, disease burden, and diagnosis history. Results were stratified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 46 publications
(51 reference statements)
1
42
0
1
Order By: Relevance
“…Increased delay to diagnosis has been associated with worse outcomes in axSpA; a recent systematic review found that individuals with a delayed diagnosis had higher disease activity, worse physical function, increased structural damage, greater likelihood of work disability, and higher direct and indirect healthcare costs than those who received earlier diagnosis [ 13 ]. Delayed diagnosis is associated with an increased likelihood for worse quality of life and negative psychological consequences [ 13 ], in addition to worse treatment outcomes [ 22 , 23 ], fatigue, difficulty sleeping and prevalence of psychosomatic disorders [ 24 ]. Several factors are independently associated with a long diagnostic delay: including female sex, HLA-B27 negativity, presence of psoriasis and young age of symptom onset [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased delay to diagnosis has been associated with worse outcomes in axSpA; a recent systematic review found that individuals with a delayed diagnosis had higher disease activity, worse physical function, increased structural damage, greater likelihood of work disability, and higher direct and indirect healthcare costs than those who received earlier diagnosis [ 13 ]. Delayed diagnosis is associated with an increased likelihood for worse quality of life and negative psychological consequences [ 13 ], in addition to worse treatment outcomes [ 22 , 23 ], fatigue, difficulty sleeping and prevalence of psychosomatic disorders [ 24 ]. Several factors are independently associated with a long diagnostic delay: including female sex, HLA-B27 negativity, presence of psoriasis and young age of symptom onset [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors are independently associated with a long diagnostic delay: including female sex, HLA-B27 negativity, presence of psoriasis and young age of symptom onset [ 25 ]. Previous misdiagnosis of FM and psychosomatic disorders is suggested to be higher in women compared with men (20.7 vs 6.6% and 40.8 vs 23.0%, respectively) [ 24 ]. Presence of peripheral arthritis and IBD have been associated with earlier diagnosis [ 26–28 ]—earlier diagnosis and treatment leading to better outcomes and treatment responses [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Survey participants in the United States aged ≥18 years with a self-reported diagnosis of PsA were recruited for our study via CreakyJoints (https://creakyjoints.org), ArthritisPower (https://arthritispower.creakyjoints.org), and social media outreach in a process similar to a previously reported survey of patients with ankylosing spondylitis [19]. The Global Healthy Living Foundation (GHLF) is the umbrella organization of both CreakyJoints and ArthritisPower, and GHLF investigators identified eligible members based on profile information, which was voluntarily provided, including age, sex, location via zip code, condition, and current medical prescription; no personal information was stored.…”
Section: Data Source and Study Variablesmentioning
confidence: 99%
“…The estimated delay between symptom onset and diagnosis of ankylosing spondylitis in the United States is approximately 13 years [24]. This delay in diagnosis contributes to the significant burden on patients, caregivers, and society [2530]. Reasons for delayed diagnosis are intrinsic to the disease and systemic to the healthcare system.…”
Section: Axial Spondyloarthritis and Barriers To Early Diagnosismentioning
confidence: 99%
“…Reasons for delayed diagnosis are intrinsic to the disease and systemic to the healthcare system. Intrinsic features of the disease such as the common presentation of low back pain [29], lack of awareness of differential disease presentations among men and women [3134], insidious onset, slow progression, lack of specific biomarkers [21,35,36], absence of remarkable physical findings among patients with early stages of axSpA and ankylosing spondylitis [37], and lack of extra-articular manifestations [37] contribute to misdiagnosis [25] and complicate early identification and diagnosis. The lack of accessibility to rheumatologists and long waiting times are also barriers to a timely diagnosis [38,39].…”
Section: Axial Spondyloarthritis and Barriers To Early Diagnosismentioning
confidence: 99%